Validation of GPS and accelerometer technology in swimming - Beanland, E.; Main, L.; Aisbett, B.; Gastin, P.; Netto, Kevin (Elsevier Australia, 2014)
Objectives: To evaluate the validity of an integrated accelerometer and Global Positioning System (GPS) device to quantify swimming kinematics variables in swimming. Design: Criterion validation study. Methods: Twenty-one sub-elite swimmers completed three 100 m efforts (one butterfly, breaststroke and freestyle) in an outdoor 50 m Olympic pool. A GPS device with an integrated tri-axial accelerometer was used to obtain mid-pool velocity and stroke count of each effort. This data was compared to velocity and stroke count data obtained from concurrently recorded digital video of the performance. Results: A strong relationship was detected between the accelerometer stroke count and the video criterion measure for both breaststroke (r > 0.98) and butterfly (r > 0.99). Also, no significant differences were detected between the GPS velocity and video obtained velocity for both freestyle and breaststroke. There was a significant difference between the GPS velocity and criterion measure for butterfly. Acceptable standard error and 95% limits of agreement were obtained for freestyle (0.13 m s-1, 0.36 m s-1) and breaststroke (0.12 m s-1, 0.33 m s-1) compared to butterfly (0.18 m s-1, 0.50 m s-1). Relative error measurements ranged between 10.2 and 13.4% across the three strokes. Conclusions: The integrated accelerometer and GPS device offers a valid and accurate tool for stroke count quantification in breaststroke and butterfly as well as measuring mid-pool swimming velocity in freestyle and breaststroke. The application of GPS technology in the outdoor training environment suggests advantageous practical benefits for swimmers, coaches and sports scientists.